Evaluation of Antibacterial Activity of Salvia stepposa Extracts Isolated using Microwave Extraction, Growing Wild in Kazakhstan - Levaya , Yana Konstantinovna; Erkenuly, Zholdasbaev Musa; Abdulkhakimovna, Atazhanova Gayane; Boltabaevna , Akhmetova Saule (Trends in Sciences, 2022)
The studies on antibacterial activity of 16 samples of Salvia stepposa (steppe sage) ethanolic extracts, an indigenous plant of Central Kazakhstan, against Staphylococcus aureus (ATCC 6538), Bacillus subtilis (ATCC 6633), Escherichia coli (ATCC 25922), Candida albicans (ATCC 10231) were assayed. Leaves and flowers of Salvia stepposa were extracted by ethanol 30, 40, 70 and 90 % using conventional and microwave extraction. Antibacterial screening performed by disc-diffusion method was conducted, the concentration of all extracts was 100 mg/mL. The results revealed that the highest activity against Staphylococcus aureus and Bacillus subtilis have leaves and flowers extract of steppe sage in all solvents except 70 % microwave leaf extract. The only extract that showed antibacterial activity against all strains of microorganisms used is 40 % microwave leaf extract of steppe sage with growth inhibition zones for Staphylococcus aureus 23.5 0.65 mm, for Bacillus subtilis 38 1.3 mm, for Escherichia coli 16.5 1.72 mm, for Candida albicans 16 2.6 mm, respectively. Was found that 70 % of leaf extract of the steppe sage obtained under microwave irradiation has the lowest activity. The MIC values for tested extracts were evaluated too. HIGHLIGHTS Salvia stepposa is a widespread plant on the territory of Kazakhstan the properties of which still remain unexplored Antibacterial activity and MIC of 16 examples obtained different methods was evaluated MAE is an interesting alternative to CE of extracting plant raw materials, which can reduce extraction time and energy consumption